Politeness in Addressing and Requesting Used by the Salespersons to the Customers at UMC E-commerce - Aurellia Calista; Esther H. Kuntjara (Institute of Research and Community Outreach - Petra Christian University, 2023)
This study examines politeness in addressing and requesting used by salespersons to customers at UMC E-commerce. This study used the first-order politeness theory by Watts (2003), supported by Indonesian (Javanese) politeness theories by Suseno (2003) and Kuntjara (2012). This qualitative study analyzed salespersons’ utterances in the conversations with their customers when delivering promotions. The findings showed that salespersons adhere to Indonesian (Javanese) politeness principles, namely respect and harmony. They employed various address terms, whether to address or as second-person pronouns, which showed politeness. In request, they showed politeness by using words or adverbs of possibility, apologies, asking for permission, and asking for help. Two possible reasons behind the use of politeness were the salespersons as the company representatives and the need to fulfill sales targets. However, for several reasons, some findings were not in accordance with Indonesian (Javanese) politeness principles. Overall, the findings indicated that politeness depends on cultural contexts.